2022
DOI: 10.1063/5.0070004
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast time- and angle-resolved photoemission spectroscopy with widely tunable probe photon energy of 5.3–7.0 eV for investigating dynamics of three-dimensional materials

Abstract: Time- and angle-resolved photoemission spectroscopy (TrARPES) is a powerful technique for capturing the ultrafast dynamics of charge carriers and revealing photo-induced phase transitions in quantum materials. However, the lack of widely tunable probe photon energy, which is critical for accessing the dispersions at different out-of-plane momentum kz in TrARPES measurements, has hindered the ultrafast dynamics investigation of 3D quantum materials, such as Dirac or Weyl semimetals. Here, we report the developm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…In TrARPES, the maximum photon energy generated from the fourth harmonic generation (FHG) of the BBO crystal is 6.3 eV, , which is not sufficient to access the Dirac node yet. The KBBF crystal can extend the FHG output to 7.0 eV, and a continuously tunable photon source covering 5.6–7.0 eV has been used in static laser-based ARPES measurements. , Here we develop its time-resolved version to facilitate ultrafast dynamic studies of 3D materials as shown in Figure d (see more details in ref ). A laser beam with a tunable wavelength of 710–930 nm and a pulse duration of 50–80 fs is generated from a Ti:sapphire oscillator and split into pump and probe beams.…”
mentioning
confidence: 99%
“…In TrARPES, the maximum photon energy generated from the fourth harmonic generation (FHG) of the BBO crystal is 6.3 eV, , which is not sufficient to access the Dirac node yet. The KBBF crystal can extend the FHG output to 7.0 eV, and a continuously tunable photon source covering 5.6–7.0 eV has been used in static laser-based ARPES measurements. , Here we develop its time-resolved version to facilitate ultrafast dynamic studies of 3D materials as shown in Figure d (see more details in ref ). A laser beam with a tunable wavelength of 710–930 nm and a pulse duration of 50–80 fs is generated from a Ti:sapphire oscillator and split into pump and probe beams.…”
mentioning
confidence: 99%
“…A combination of two β-BaB 2 O 4 (BBO) crystals is used to generate probe pulses with a wavelength at 205 nm to realize high time and energy resolution, and an optional combination of a BBO and a KBe 2 BO 3 F 2 (KBBF) crystal is used to generate probe pulses with a wavelength longer than 185 nm in air to reach higher probe photon energy. In a recent study, the KBBF crystal is used to extend the wavelength of the probe laser pulse to 177 nm in the vacuum chamber [51].…”
Section: Time-and Angle-resolved Photoemission Spectroscopymentioning
confidence: 99%
“…Thus, our tomographic data cover ≈39% of the BZ volume. For crystalline materials with smaller k z dimensions, particularly layered 3D electron materials, 9,10,17,34 larger portions of the bulk BZ or entire bulk BZs can be scanned. Similarly, for layers of 3D molecules, 62 3D orbital momentum tomograms can be recorded.…”
Section: B Multispectral Energy-momentum Mappingmentioning
confidence: 99%
“…Over the past fifteen years, trARPES has evolved into a powerful ARPES modality providing direct dynamical information on electronic structure at the fundamental time scales of electronic and atomic motion, particularly on photoinduced transient changes of electronic states and their population. [23][24][25][26][27][28][29][30][31][32] trARPES is now routinely performed using table-top laser sources based on fourth and higher harmonic generation (HHG) in solids 33,34 and gases [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] , respectively, as well as using free-electron lasers (FELs) based on the self-amplification of spontaneous emission (SASE) of free electrons in undulators. 21 The corresponding probe photon energies in trARPES range from the far UV to soft x-rays where a sweet spot currently is the intermediate extreme ultraviolet (XUV) regime.…”
Section: Introductionmentioning
confidence: 99%